Forming Legal Culture in Customary Forest Management: Local Wisdom Approach of Customary Law Communities - I Gusti Agung Mas Rwa Jayantiari; I Gst Pt Bagus Suka Arjawa; Leonito Rebeiro; Joanne Audrey Paquita (Udayana Journal of Law and Culture, 2024)
Customary law communities in Indonesia firmly attach to customary forests in their territory. For generations, they have preserved and managed customary forests according to customary rules, either written or unwritten, that reflect local wisdom. This article aims to analyze customary law communities' local wisdom approach in forest management to realize legal compliance that reflects legal culture. It assesses local wisdom as the essential form of legal culture in customary forest management and scrutinizes efforts to strengthen local wisdom in forest management arrangements. This article reflects a socio-legal method that explores relevant statutory regulations and their implementation in society. The research and analysis suggest that the legal culture of customary law communities takes the form of compliance in managing forests due to the local wisdom they have internalized from generation to generation. Local wisdom in various regions in Indonesia is integrated with local rules that align with the function of customary law to create social order. It has also been found that several regional governments in Indonesia have made an effort to strengthen local wisdom. The regional government's recognition of the status of customary law communities as the actors in customary forest management has legitimated the local wisdom in protecting customary forests.